Keadaan Suara Hati dalam Mengambil Suatu Keputusan - Megawati Naibaho; Pankrasia Niasti Sarumaha; Alexius Poto Obe (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2023)
God created human being and endowed with a conscience. Conscience has a very important role to guide humans to make the right decisions. Through help of conscience, humans are able to know what is good and do it. One of the questions to be answered in this article what are the states of conscience in order to make a good and right decision. This paper uses a qualitative approach through literature studies using various theological point of view and reflection. From this research, it was found that human’s existence as a creation has conscience to enables humans to make good and right decisions. Humans are expected to be able to use intention properly and responsibly. In making a right decision, humans need to analyze, evaluate, species and make choices with freely and responsibly. The Holy Spirit plays a significant role for guiding to make a decision. Conscience is a practical decision of the mind that can help to make wise decision. Conscience can also be mistaken because of a lack of knowledge and understanding, and there is a neglect of conscience. As a result, the decisions taken are not in accordance with God's will. Realizing the importance of the role of conscience in determining decisions, it is necessary to develop a conscience. Conscience is the most secret human core, personal and being a holy sanctuary as place where human being in silent with God.